Perceived Social Support Through ICT Among Spanish and Italian Teachers: A Qualitative Study - Garzotto, María Elena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The teaching profession is characterized by a high risk of stress and burnout. This paper presents the results of a qualitative study, whose objectives are to identify how teachers perceive social support in the professional context, to know how this influences the perception of teacher well-being and to deepen this support through ICT and social networks during COVID 19. This study used interviews as a means of data collection. The results highlight the importance of perceived social support for teacher well-being and sense of belonging.